The Influence of Quantum Teaching Learning Model Assisted Digital Media (Edmodo) Toward Science Literature and Self-Efficiency of Highschool Students - Agus Muliaman; Henni Fitriani; Khaira Usrati; Mirnawati Mirnawati (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine the effect of the Quantum Teaching learning model assisted by digital media (edmodo) on scientific literacy and self-efficacy. The type of research conducted is experimental research using a pretest-posttest control group design. The population in this study included all students of class X SMA Negeri 1 Muara Batu. The sampling technique used is purposive sampling. The sample in this study is class X MIPA 1 as the experimental class and X MIPA 2 as the control class. The experimental class was treated using the Quantum Teaching learning model while the control class was treated using the conventional learning model. The results of student literacy were obtained through a scientific literacy test instrument that had been validated and student self-efficacy was obtained through the provision of a valid student self-efficacy assessment questionnaire. Hypothesis testing in this study using independent sample t-test. The results of the t-test results of scientific literacy have a sig value of 0.038 <0.05 and the t-test results for students' self-efficacy have a sig value of 0.045 <0.05. So that H0 is rejected and Ha is accepted, in other words this means that there is a significant influence of the Quantum teaching learning model assisted by digital media (Edmodo) on the results of scientific literacy and self-efficacy of high school students.